Wave blocking system suitable for ultra-wideband power line carrier communication - REN GEWU; WANG JIE; WANG XIUPANG; ZHU TONG; LI YONG; WANG BAIBING; WU LIN; YANG SHUANGYU; GUO XUELI; PENG YONG (2025)
The invention discloses a wave blocking system suitable for ultra-wideband power line carrier communication, and belongs to the technical field of communication wave blocking, the wave blocking system comprises a power line, the power line is connected in series with a magnetic sleeve damper and a box body, the box body is internally provided with a wideband wave blocking module, and the power line is connected in parallel with a protection element. According to the invention, the broadband wave-blocking module effectively blocks the leakage of middle and low frequency band signals in the frequency band of 1.6-86 MHz, the magnetic sleeve damper and the reflection line segment between the magnetic sleeve damper act together, the function of blocking the leakage of middle and high frequency band signals in the frequency band of 1.6-86 MHz by the broadband wave-blocking module is enhanced, and the magnetic sleeve damper, the reflection line segment and the broadband wave-blocking module are combined, so that the